Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22073592
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Associated Long TSLP Inhibits the Production of IgA

Abstract: Thymic stromal lymphopoietin (TSLP) contributes to asthmatic disease. The concentrations of protective IgA may be reduced in the respiratory tract of asthma patients. We investigated how homeostatic short TSLP (shTSLP) and asthma-associated long TSLP (loTSLP) regulate IgA production. B cells from healthy donors were stimulated in the presence or absence of shTSLP or loTSLP; the concentrations of IgA, IgM, IgE, and IgG antibodies were determined in cell culture supernatants; and B cells were analyzed by flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, since the expression patterns and biological properties of these two different isoforms of TSLP seem to be distinct, these two TSLP isoforms should be analyzed separately in future studies. This is highlighted by findings in asthma research, where it was observed that the asthma-associated long TSLP isoform negatively regulates the secretion of IgA, potentially impacting the surveillance of mucosal surfaces detrimentally in this condition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the expression patterns and biological properties of these two different isoforms of TSLP seem to be distinct, these two TSLP isoforms should be analyzed separately in future studies. This is highlighted by findings in asthma research, where it was observed that the asthma-associated long TSLP isoform negatively regulates the secretion of IgA, potentially impacting the surveillance of mucosal surfaces detrimentally in this condition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…An asthma-associated long form of TSLP is produced by epithelial cells following viral infection. It inhibits the production of IgA antibodies, which are believed to neutralise viruses at mucosal surfaces [ 48 ]. Viral infection also disrupts junctional complexes and inhibits wound repair, further reducing barrier integrity and driving the cycle of epithelial damage [ 49 51 ].…”
Section: Airway Epithelial Barrier Disruptionmentioning
confidence: 99%
“…Retinoic acid also promotes the production of IgA in the presence of loTSLP and may, thus, be able to restore IgA production in asthma patients in the presence of aberrant TSLP signaling. The addition of shTSLP or loTSLP did not affect B cell proliferation, neither in the presence nor the absence of CphosphodiestericG (CpG) [ 48 ].…”
Section: Tslp In Epithelium-driven Airways Inflammationmentioning
confidence: 99%